Do members of staff in a medium secure unit recognise the signs of dementia and know how to manage it accordingly? - Uczniak, Alicyja (2017)
The aims of this study were to explore the experiences, awareness and attitudes of members of staff working within a Medium Secure Unit (MSU) regarding older patients, specifically whether they recognise and manage signs of dementia and other age-associated risks. An initial scoping exercise was conducted to substantiate the rationale for the study then inform the content of two focus groups. Each focus group was representative of a staffing group: the first of nursing staff and the second of allied health professionals. The focus groups had the same content, but were conducted sequentially. A thematic analysis was conducted after each group to compare and combine the content using an iterative process. An over-arching theme identified through thematic analysis was forensic risk. The other main themes were: vulnerability of older adults, organisational factors, lack of awareness and recognition, interventions and staff attributions. Differences between the staff groups are explored, with observed differences between their use of reflective practice and supervision. Implications regarding risk management, staff training, supervision and the model of care are discussed.